Horizon of expectation of title in (necklace) by Sherko Bekas - جەلال عزیز سامان; بەختیار محمد رؤف ڤان (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
This thesis converses about the horizon of expectations or in other words, horizon of waiting, as a concept in the aesthetics of reception theory and the title of a work of art, and the effects that puts on the horizon of expectations in the aesthetics of reception theory. The first part of the thesis is focusing on the theoretical concept of the horizon of expectation and the horizon change in the aesthetics of reception theory. The second par is the practical part, which focuses on the title of a book by Sherko Bekas under the title (Necklace) and the aspects of effects that this title puts on the reader’s horizon of expectations.